Comitê de ética em pesquisa com seres humanos da Universidade Federal de Santa Maria: uma investigação acerca de percepções de seus usuários - Heinz, Gabriela (2021)
Initially, motivated by the discoveries of the atrocities that occurred in experiments during World War II, research ethics became a recurrent theme in the scientific environment. It aims to guide researchers in conducting their activities in order to protect research participants against possible risks and harms and also to ensure the potential benefits, with social return. In this sense, the National Health Council, through its Resolutions, established in 1996 the National Commission on Research Ethics (CONEP) to manage the Research Ethics Committees (CEPs), which evaluate research projects involving human beings. Considered relatively young, the system still generates doubts and questions from its users, as well as difficulties regarding the formalization of projects with the Platform Brazil. Based on this context, it was defined as the objective of this study to know the perceptions of users in relation to the performance of CEP/UFSM. A case study was developed with data obtained through 376 opinions issued by the CEP, in the period from 2016 to 2019, and questionnaires applied to users, via Google Forms platform that obtained the return of 187 respondents. Content analysis was performed on the documentation surveyed, and the quantitative data from the respondents were analyzed using descriptive and factor statistics. The main pending issues found in the opinions are related to aspects of the Informed Consent Form (ICF), methodology, necessary formalities in the other mandatory documents and discordant information provided in the project, Plataforma Brasil and attached documents. Regarding the perceptions of users, it was found that with the exception of those who belong to the Health area, they do not feel that the specifics of their research are contemplated in the Resolutions issued by the CNS, even so, in general, there is understanding about what is ethics in research and why it is important. The main difficulty perceived in the process of submission and approval of a project is the use of the Platform Brazil, followed by the preparation of documents and obtaining institutional authorization. Despite the difficulties the respondents consider the CEP's quick return in evaluating the projects and find it easy to obtain information from the Committee, in addition, they consider the opinions issued clear and objective. It is concluded that the conduct of the operationalization of activities in the CEP/UFSM has acceptance by its users, but they lack training activities on the use of Platform Brazil, preparation of documents and legislation, especially in areas of specific knowledge.